AKAD MURABAHAH DAN PERMASALAHANNYA DALAM PENERAPAN DI LKS - Fasiha Kamal (MUAMALAH, 2015)
Murabahah emphasis on margins that affect the formation of prices. If the margin is high, murabaha financing will not be attractive to customers, it should be a murabaha financing solutions for customers who have been doing a conventional bank loan. Murabaha financing has been the development of the concept of the classical fiqh. and Murabahah certainly not without the risks faced as a result of the business risk management procedures necessary to mitigate and minimize the risks arising